Evaluation of key performance indicators of logistics firms - Gözaçan, Nazlican (Logistics and sustainable transport, 2020)
Key Performance Indicators (KPI) has been outlined for implementing total quality management (TQM) across logistics sector. This study constituted on the quality values of logistics firms in the logistics sector, which is examined with key performance indicators through the integrated method of Analytic Hierarchy Process (AHP) and SMART Goal Setting. The calculations were performed for logistics firms. The method used in this study is the integrated method of the AHP Method and SMART Goal Setting. The results highlight the most mentioned key performance indicators in the literature in a prioritized version also during the prioritizing process via AHP Method, the SMART Goal Setting approach also is applied.
Keywords: analitični hierarhični proces; analytic hierarchy process (AHP); celoten menedžment kakovosti; kazalniki uspešnosti; key performance indicators (KPI); SMART goal setting; total quality management; zastavljeni cilji